2015
DOI: 10.1021/acsmacrolett.5b00483
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Photocontrol of Block Copolymer Morphology During Dip-Coating of Thin Films

Abstract: We demonstrate a unique combination of simultaneous top-down and bottom-up control of the morphology of block copolymer films by application of in situ optical irradiation during dip-coating. A light-addressable and blockselective small molecule, 4-butyl-4'-hydroxyazobenzene (BHAB), is introduced into a diblock copolymer of polystyrene and poly(4-vinylpyridine) (PS-P4VP) of 28.4 wt% P4VP via supramolecular chemistry, notably by hydrogen bonding to P4VP. We show that the spherical morphology of thin films dip-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13] Supramolecular cooperative motion (SMCM) plays an important role in the self-assembly process of LCBCs, driven by the interplay functions between the MPS and the elastic deformation of liquid crystal (LC) ordering. [14][15][16][17][18][19][20] Recent researches have realized the fabrication of sub-10 nm microstructures by supramolecular interactions www.advancedsciencenews.com www.mrc-journal.de…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13] Supramolecular cooperative motion (SMCM) plays an important role in the self-assembly process of LCBCs, driven by the interplay functions between the MPS and the elastic deformation of liquid crystal (LC) ordering. [14][15][16][17][18][19][20] Recent researches have realized the fabrication of sub-10 nm microstructures by supramolecular interactions www.advancedsciencenews.com www.mrc-journal.de…”
Section: Introductionmentioning
confidence: 99%
“…With a relatively high Flory–Huggins parameter (χ) and controllable responsiveness upon microphase separation (MPS), liquid‐crystalline block copolymers (LCBCs) have been utilized to fabricate multimorphologic nanostructures, such as sphere, cylinder, double gyroid, and lamella, depending on the volume ratio of each block . Supramolecular cooperative motion (SMCM) plays an important role in the self‐assembly process of LCBCs, driven by the interplay functions between the MPS and the elastic deformation of liquid crystal (LC) ordering …”
Section: Introductionmentioning
confidence: 99%
“…relative to the pyridine repeat units. 156 Normally, dip-coating of such supramolecular solutions without illumination at slow dip-coating rates gives rise to films whose small-molecule content is much lower than in solution but increases with increasing dip-coating rate, as observed also with BHAB. This led to a change in film morphology from spherical to cylindrical at a dip-coating rate of around 1.0 mm min À1 for the system studied.…”
Section: Photocontrol Of Micro-and Nanostructures Through Supramolecumentioning
confidence: 93%
“…69 Recently, Vapaavuori et al demonstrated that the BCP morphology of a thin film containing a block-selective hydrogenbonding azobenzene can be manipulated with light. 156 As explanatory background, some of the authors had previously shown that when the films are prepared using the dip-coating technique (i.e. where a substrate is pulled out of the polymer solution at a given rate), the hydrogen-bonding small molecule content in the film is controlled by solution azo/polymer repeat unit ratio, dip-coating withdrawal speed, and the solvent used.…”
Section: Photocontrol Of Micro-and Nanostructures Through Supramolecumentioning
confidence: 99%
“…In a recent communication, we demonstrated that the thin film surface nanopattern, SM content, and thickness can be modified by visible light illumination of a film during slow dip-coating from a supramolecular BCP solution containing a photoactive azo-based guest SM. 28 Since light provides very precise spatial and temporal control, this in-situ photocontrol points to pathways for producing complex spatially varying surface patterns.…”
Section: Introductionmentioning
confidence: 99%